The Impact of Climate Change on the Spread of Viruses and the Emergence of New Diseases - Sahib, Amjed Mohammed; Meri, Marwa Ahmed; Madfoon, Zainab Mohammed (Medical Science Journal for Advance Research, 2025)
The planet faces an unprecedented climate change because global temperatures have risen heavily while rainfall patterns have shifted. The occurrence of extreme events like hurricanes droughts along with floods has significantly increased. All aspects of economy and health and ecology remain susceptible to serious threats as a result of climate changes. Scientific studies conducted by the Intergovernmental Panel on Climate Change (IPCC, 2021) show that human actions through greenhouse gas emissions lead to these changes by releasing carbon dioxide and methane. The detected health problems and environmental deterioration produced by these transformations led to more infectious disease outbreaks and the generation of modern diseases.